2011
DOI: 10.1016/j.talanta.2011.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the oxidation stability of biodiesel and oils by spectrofluorimetry and multivariate calibration

Abstract: Oxidation stability is an important quality parameter for biodiesel. In general, the methods used to evaluate the oxidation stability of oils and biodiesels are time-consuming. This work reports the use of spectrofluorimetry, a fast analytical technique, associated with multivariate data analysis as a powerful analytical tool to prediction of the oxidation stability. The prediction of the oxidation stability showed a good agreement with the results obtained by the EN14112 reference method Rancimat. The models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 16 publications
0
24
0
6
Order By: Relevance
“…Therefore, the degree of oxidation of biodiesel is a major concern for biodiesel producers. The main driving force of the oxidation process is the presence of double bonds 8 in the chemical structure of the mono-alkyl esters. The oxidation process begins with the loss of hydrogen atoms from the chemical structure that subsequently leads to formation of alkyl-radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the degree of oxidation of biodiesel is a major concern for biodiesel producers. The main driving force of the oxidation process is the presence of double bonds 8 in the chemical structure of the mono-alkyl esters. The oxidation process begins with the loss of hydrogen atoms from the chemical structure that subsequently leads to formation of alkyl-radicals.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Meira et al 11 demonstrated that fluorescence spectroscopy coupled with multivariate analysis can be used as an analytical tool to evaluate the oxidative stability of biodiesel and soybean oil in accordance with the conventional Rancimat method. 11 These authors have also identified the adulteration of biodiesel with vegetable oil using fluorescence spectroscopy. [10][11][12] Biodiesel is chemically defined as a mixture of mono-alkyl esters of long-chain fatty acids (C16-C18) derived from vegetable oils and animal fats.…”
Section: Introductionmentioning
confidence: 99%
“…11 These authors have also identified the adulteration of biodiesel with vegetable oil using fluorescence spectroscopy. [10][11][12] Biodiesel is chemically defined as a mixture of mono-alkyl esters of long-chain fatty acids (C16-C18) derived from vegetable oils and animal fats. It is a domestic renewable fuel for diesel engines and meets the standards and specifications provided by the American Society for Testing and Materials (ASTM D 6751).…”
Section: Introductionmentioning
confidence: 99%
“…O nosso país é o segundo maior produtor deste biocombustível atualmente sendo superado apenas pelos Estados Unidos (MARKET PUBLISHERS, 2014). O biodiesel tem várias vantagens em relação ao diesel, como, biodegradabilidade, lubricidade superior, renovabilidade, não-toxicidade e mínimo teor de enxofre (MEIRA et al, 2011;YUSUF et al, 2011).…”
Section: Introductionunclassified